A comparative study of atropine and atropine plus pralidoxime in the management of organo-phosphorous poisoning - Baruah, Sreemanta M.; Das, John K.; Hossain, Imdadul; Singh, Nongmaithem B. (International Journal of Advances in Medicine, 2023)
Background: Poisoning with organophosphorus compounds (OP) is a common problem throughout the world particularly in developing countries. Standard treatment involves resuscitation, administration of the anti-muscarinic agent atropine, an acetylcholinesterase reactivator (pralidoxime) and assisted ventilation if necessary. In this study we compared the efficacy of add-on pralidoxime therapy over therapy with atropine alone in OP poisoning. Methods: The study included 103 patients, out of 103 OP poisoning cases, 54 patients received both atropine and PAM (group A) and 49 received only atropine (group B). Main outcome parameters of the study were total hospital stay and mortality. The data was compared using ‘t’ test while mortality was compared using Fisher’s exact test. Data was tabulated, analysed, reviewed and evaluated. Results: There was no difference in duration of hospital stay between the two group. The mean hospital stay in group A was 3.71±1.92 days and in group B was 3.14±2.01 days (p value >0.05). No difference in mortality was seen between the two group. Out of 54 in group A, 8 died and in group B out of 49, 7 died (p value >0.05). Importantly cost burden is very high in the pralidoxime added group. Conclusions: There is no significant difference in use of atropine alone or atropine-pralidoxime combination in terms of morbidity and mortality in OP poisoning rather the later incurs more economic burden which may not be practicable in poor countries like India. However, a larger multicentric prospective study needs to be conducted, to be able to draw a definitive conclusion.